The works of edgar allan poe ebook - Poe, Edgar Allan (Duke Classics, 2014)
It is virtually impossible to overstate Edgar Allan Poe's importance in the field of American literature. He is credited not only with inventing or significantly advancing the short story, detective fiction, and science fiction, but also with being one of the first Americans to pursue a career in writing as a vocation. This comprehensive volume is a career-spanning collection of Poe's stories and poems.